Acute duodenal obstruction is a rare complication of gallstone disease - V. K. Koryttsev; S. S. Skupchenko; A. M. Krasnoslobodtsev (Вестник хирургии имени И.И. Грекова)
The article describes a rare complication of gallstone disease – vesicoduodenal fistula. This complication is accompanied by the release of a large concrement into the lumen of the duodenum. Subsequently, the migration of the concrement leads to the development of small bowel obstruction. The present clinical observation presents the early diagnosis and successful treatment of an elderly patient with severe concomitant pathology before the development of the clinic of small bowel obstruction.